2022
DOI: 10.3390/vaccines10071140
|View full text |Cite
|
Sign up to set email alerts
|

Relative Vaccine Effectiveness of the Third Dose of CoronaVac or BNT162b2 Following a Two-Dose CoronaVac Regimen: A Prospective Observational Cohort Study from an Adult Vaccine Center in Turkey

Abstract: Coronavirus disease 2019 (COVID-19) continues to pose a threat to public health with the potential for the emergence of new variants. Vaccines are the milestones to control and slow down the damage of the pandemic. As of January 2021, a two-dose regimen with CoronaVac was authorized in Turkey. Due to the waning seroprevalence rate of SARS-CoV-2 over time, BNT162b2 or CoronaVac has been administered as the third dose following a two-dose CoronaVac regimen as a national vaccination policy. As of 14 January 2021,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Another study reported higher vaccine effectiveness with a heterologous booster dose of inactivated COVID-19 vaccine [36]. The favorable effect of the heterologous booster over a homologous one was supported in a study from Türkiye, which reported higher efficacy with CoronaVac when boosted with an mRNA as compared to the third dose of CoronaVac [37]. Yue et al [38] reported that a single booster dose of inactivated SARS-CoV-2 vaccine also has an impact on the Delta variant.…”
Section: Discussionmentioning
confidence: 95%
“…Another study reported higher vaccine effectiveness with a heterologous booster dose of inactivated COVID-19 vaccine [36]. The favorable effect of the heterologous booster over a homologous one was supported in a study from Türkiye, which reported higher efficacy with CoronaVac when boosted with an mRNA as compared to the third dose of CoronaVac [37]. Yue et al [38] reported that a single booster dose of inactivated SARS-CoV-2 vaccine also has an impact on the Delta variant.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that following priming with two doses of CoronaVac vaccination, a heterologous mRNA booster is more immunogenic than a homologous booster (15,(19)(20)(21)(22)(23)(24)(25) (21) found that the heterologous vaccination strategy "CoronaVac and BNT162b2 regimen" was able to induce a stronger humoral immune response. However, the effect of a second BNT162b2 booster was not evaluated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many countries have implemented a booster dose of vaccine 6 . Since July 1, 2021, the Turkish Ministry of Health has offered a third (booster) dose of vaccine, with either the CoronaVac or BNT162b2 vaccine, at least 3 months after the second dose of COVID-19 vaccine 7 .…”
Section: Introductionmentioning
confidence: 99%